2020
DOI: 10.1021/acs.organomet.0c00204
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Luminescent Bis(isocyanoborato) Rhenate(I) Complexes as a Selective Sensor for Cyanide Anion

Abstract: A series of luminescent bis(isocyanoborato) rhenate-(I) phenanthroline complexes with the general formula of cis,trans-[Re(CO) 2 (CNBR 3 ) 2 (phen)]K (R = C 6 F 5 and C 6 H 5 ) have been designed and synthesized. The solutions of these complexes exhibit MLCT phosphorescence. Detailed anion titration study showed that the emission intensity of bis(isocyanotriphenylborato) complex in CH 3 CN/H 2 O solution would be significantly decreased in the presence of cyanide anion, while such a change would not be observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…As noted above, many prior investigations of cyanoborylated complexes have focused on 5d metals, [55][56][57][58][59]61,64 where the ligand field splitting is inherently larger than in 4d metals and thermal population of the 3 MC from the 3 MLCT state is therefore less important. Thus, it is not too surprising that the effect illustrated by Figure 6 has been unnoticed until now.…”
Section: Uv−vis Absorption and Luminescence Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted above, many prior investigations of cyanoborylated complexes have focused on 5d metals, [55][56][57][58][59]61,64 where the ligand field splitting is inherently larger than in 4d metals and thermal population of the 3 MC from the 3 MLCT state is therefore less important. Thus, it is not too surprising that the effect illustrated by Figure 6 has been unnoticed until now.…”
Section: Uv−vis Absorption and Luminescence Propertiesmentioning
confidence: 99%
“…Important prior work on isocyanoborato complexes focused on 5d metals including Ir­(III), Re­(I), and Os­(II) as well as on Ni­(II), Pd­(II), Pt­(II), Cu­(I), , and Ag­(I) . Very recently, Ru­(II) and Fe­(II) isocyanoborato complexes were studied in the context of electrochemistry and spectroscopy, but their photoreactivity and photochemistry have not yet been reported. Attachment of B­(C 6 F 5 ) moieties to the cyanide ligands of heteroleptic complexes with α-diimine chelates usually results in the stabilization of the metal-centered d orbitals, whereas the diimine π* orbitals are less affected .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Of interest is that BCF/BPh3 adducts of heteroleptic Re(I) diimine carbonyls have shown promise as selective sensors for cyanide anion. 44 Most recently, Wenger et al have boronated heteroleptic Ru(II) and Ir(III) diimine complexes and demonstrated their high activity for energy transfer and photoredox catalysis. 45,46 Studies of cyanometallates have been driven by the promise of applications in magnetic materials involving single-molecule/Prussian-Blue analogues and in electrode materials for solid-state batteries.…”
Section: N-methylpyrrolidinonementioning
confidence: 99%
“…Currently, anion sensors have been the subject of considerable interest for their numerous roles in various processes in the fields of biology, catalysis, industry, and environmental protection. Anion sensors have also been used in devices such as television screens, as well as in monitoring and microelectronic sensors [1][2][3][4][5]. Researchers are interested in anion sensors with different dimensional structures, such as 2-and 3-dimensional patterns on carbon nanotubes and MOF structures [6,7].…”
Section: Introductionmentioning
confidence: 99%